Acute Mitral Regurgitation due to Ruptured ePTFE Neo-chordae - Coutinho, GF (2007)
Chordal replacement with expanded polytetrafluoroethylene (ePTFE) sutures has proven to be a simple, versatile, and durable technique for the treatment of prolapsed cusps causing mitral valve regurgitation. ePTFE is known for its strong resistance to tension, and is judged to be unbreakable under physiological conditions. Herein are reported two cases of rupture of synthetic chordae tendineae; the possible causes of this extremely rare finding are analyzed.